H-NS family protein MvaU downregulates phenazine-1-carboxylic acid (PCA) biosynthesis via binding to an AT-rich region within the promoter of the phz2 gene cluster in the rhizobacterium Pseudomonas strain PA1201 - Yun-Ling Fang; Ying Cui; Lian Zhou; Chitti Thawai; Tatheer Alam Naqvi; Hong-Yan Zhang; Ya-Wen He (My University, 2021)
Histone-like nucleoid-structuring (H-NS) proteins are key regulators in gene expression silencing and in nucleoid compaction. The H-NS family member proteins MvaU in Pseudomonas aeruginosa are thought to bind the same AT-rich regions of chromosomes and function to coordinate the control of a common set of genes. Here, we explored the molecular mechanism by which MvaU controls PCA biosynthesis in P. aeruginosa PA1201. We present evidence suggesting that MvaU is self-regulated. Deletion of mvaU significantly increased PCA production, and PCA production sharply decreased when mvaU was over-expressed. MvaU transcriptionally repressed phz2 cluster expression and consequently reduced PCA biosynthesis. β-galactosidase assays confirmed that base pairing near the −35 box is required when MvaU regulates PCA production in PA1201. Electrophoretic mobility shift assays (EMSA) and additional point mutation analysis demonstrated that MvaU directly bound to an AT-rich motif within the promoter of the phz2 cluster. Chromatin immunoprecipitation (ChIP) analysis also indicated that MvaU directly bound to the P5 region of the phz2 cluster promoter. MvaU repression of PCA biosynthesis was independent of QscR and OxyR in PA1201 and neither PCA or H 2 O 2 were the environmental signals that induced mvaU expression. These findings detail a new MvaU-dependent regulatory pathway of PCA biosynthesis in PA1201 and provide a foundation to increase PCA fermentation titer by genetic engineering.
Keywords: Phenazine; Gene cluster; Strain (injury); Bacterial Genetics and Biotechnology